Sexual differences in root growth and antioxidant characteristics in Salix viminalis exposed to cadmium stress. Issue 14 (6th December 2021) - Zou, Junzhu; Zhang, Yixin; Li, Xia; Ma, Xiaodong; Liu, Junxiang; Peng, Xiangyong; Sun, Zhenyuan
Abstract: Salix viminalis is a typical dioecious shrub willow, which has been widely used in the heavy metal polluted soil phytoremediation due to its fast growth rate, deep root system, and metal-resistance trait. It has been reported that dioecious plants present sex-specific characteristics when exposed to biotic and abiotic stress. However, different responses to heavy metal cadmium stress between male and female plants of S. viminalis have not been clarified. In this study, male and female S. viminalis clones were treated by 100 μM cadmium stress for a period of 21 days, and the root morphology, hydrogen peroxide content, malondialdehyde, and free proline content, antioxidant enzyme activities, and glutathione content were investigated after every 7-day interval. The results showed that female plants of S. viminalis developed thicker root diameter and volume and also accumulated more hydrogen peroxide than males at the first 7-day interval. Furthermore, sexual dichotomous indexes showed the most significant on the second 7-day interval. These findings suggest that male plants of S. viminalis have stronger cadmium tolerance than female plants and sexual differences in adaptive responses to cadmium are duration dependent, which adds to present evidence of sex-related responses to environmental stress in dioecious plants. Novelty statement: Salix viminalis, a dioecious shrub willow, has been widely used in phytoremediation, yet sexually differences in tolerance to cadmium of which remained unclear. This study focused on different responses to cadmium stress between roots of male and female S. viminalis . Results show that male plants of S. viminalis have stronger cadmium tolerance than female plants, which indicates male S. viminalis should be more considered to be applied for phytoremediation and ecological restoration of cadmium-accumulated soil considering cadmium tolerance characteristics. The findings can provide valuable evidence and insights for researches focused on phytoremediation with dioecious woody plants and sexual dimorphism under abiotic stress.